A Feedback Loop Involving the Phd3 Prolyl Hydroxylase Tunes the Mammalian Hypoxic Response In Vivo - Yoji Andrew Minamishima; Javid J. Moslehi; Robert F. Padera; Roderick T. Bronson; Ronglih Liao; William G. Kaelin (2009)
Hypoxia-inducible factor (HIF), consisting of a labile alpha subunit and a stable beta subunit, is a master regulator of hypoxia-responsive mRNAs. HIF alpha undergoes oxygen-dependent prolyl hydroxylation, which marks it for polyubiquitination by a complex containing the von Hippel-Lindau protein (pVHL). Among the three Phd family members, Phd2 appears to be the primary HIF prolyl hydroxylase. Phd3 is induced by HIF and, based on findings from in vitro studies, may participate in a HIF-regulatory feedback loop. Here, we report that Phd3 loss exacerbates the HIF activation, hepatic steatosis, dilated cardiomyopathy, and premature mortality observed in mice lacking Phd2 alone and produces a closer phenocopy of the changes seen in mice lacking pVHL than the loss of Phd2 alone. Importantly, the degree to which Phd3 can compensate for Phd2 loss and the degree to which the combined loss of Phd2 and Phd3 resembles pVHL loss appear to differ for different HIF-responsive genes and in different tissues. These findings highlight that the responses of different HIF target genes to changes in prolyl hydroxylase activity differ, quantitatively and qualitatively, in vivo and have implications for the development of paralog-specific prolyl hydroxylase inhibitors as therapeutic agents.